2015
DOI: 10.1039/c5gc00130g
|View full text |Cite
|
Sign up to set email alerts
|

In situ trapping of enol intermediates with alcohol during acid-catalysed de-polymerisation of lignin in a nonpolar solvent

Abstract: Acid-catalysed degradation of wood in toluene–MeOH yields the lignin monomers homovanillyl aldehyde dimethyl acetal and homosyringaldehyde dimethyl acetal selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…Barta and co‐workers reported another approach that circumvented the repolymerization of lignin by stabilizing the reactive aldehydes by their transformation into acetals upon the addition of ethyleneglycol (Figure B) . Acetal formation with methanol has also been reported . The Rh‐catalyzed in situ decarbonylation of reactive aldehydes formed during the triflate‐catalyzed cleavage of lignin was recently reported by Bruijnincx and co‐workers (Figure B) .…”
Section: Introductionmentioning
confidence: 58%
“…Barta and co‐workers reported another approach that circumvented the repolymerization of lignin by stabilizing the reactive aldehydes by their transformation into acetals upon the addition of ethyleneglycol (Figure B) . Acetal formation with methanol has also been reported . The Rh‐catalyzed in situ decarbonylation of reactive aldehydes formed during the triflate‐catalyzed cleavage of lignin was recently reported by Bruijnincx and co‐workers (Figure B) .…”
Section: Introductionmentioning
confidence: 58%
“…Watanabe and co-workers 192 ( Table 1 , entry 12) treated two types of wood species, namely eucalyptus globulus and cedar, with a catalytic amount (<1%) of sulfuric acid in a mixture of hydrophobic solvent (e.g., toluene) and alcohol (e.g., methanol) to result in homovanillyl aldehyde dimethyl acetal ( M31G ) and homosyringaldehyde dimethyl acetal ( M31S ) at 140 °C. Owing to the presence of methanol, the aromatic C2 enol ether intermediate obtained upon acid catalysis underwent acetal formation in situ.…”
Section: Catalytic Strategies Aiming At High Yield and Selective Prodmentioning
confidence: 99%
“…For example, the application of acids between 80 °C to 180°C is very effective in cleaving the β-O-4 linkage forming aldehyde and ketone fragments 7,8 . Our groups and others have recently demonstrated that acidolysis combined with the methodologies to stabilize and trap reactive fragments is extremely potent to obtain phenolic monomers with specific chemical motifs 9,10,11,12 . Of these, in particular acetal trapping of reactive aldehydes with alcohols to obtain phenolic 2-arylmethyl-1,3dioxolanes (acetals) proved powerful due to its relative simple application and the retention of the highly functionalized nature of the lignin monomers (Figure 1b) 13,14…”
Section: Introductionmentioning
confidence: 99%